Welcome to mini skirts but not to mini wages, 1968 (1968)
1968 1960-2000 "Welcome to mini skirts but not to mini wages, 1968" [EP0191], 1968 'Welcome to mini skirts but not to mini wages join the fight for equal pay the A.E.F. way' poster issued by the Amalgamated Union of Engineering and Foundry Workers and printed in their newspaper 'The Way for Women and Youth', December 1968.